Research on QoS routing method based on NSGAII in SDN. (September 2020) - Li, Daoquan; Wang, Xue; Jin, Yingnan; Liu, Haoxin
Abstract: Software Defined Network (SDN) makes routing decisions according to the shortest path. This routing scheme does not consider link information such as link residual bandwidth, forwarding delay, packet loss rate and so on. In the case of large data flow, it is easy to cause network congestion, thus reducing the network quality of service assurance. For this reason, using the ability of SDN network controller to monitor the underlying network information and control the route forwarding, we try to set multiple objective functions according to different QoS parameters, and use the non-dominated sorting multi-objective optimization genetic algorithm (NSGA II) based on the elite strategy to make routing decisions. Compared with other routing algorithms, the proposed multi-objective optimization genetic algorithm reduces forwarding delay and packet loss rate, so can effectively prevent network congestion.